Enhance Digital Branding Through Sensory Marketing in Sumberwaru Ecotourism Banyuwangi - Kukuh Judy Handojo; Agus Hermawan; Wening Patmi Rahayu (International Forum of Researchers and Lecturers, 2026)
In the current era of technological advancement on a massive scale and consumer behavior which has changed compared with five years ago also including the decision to choose a suitable destination with their expectation. Recently, consumers or visitors of tourist destinations also want their engagement in activities within the tourist attraction visited, other than their contribution will be used for seeking validation from their social environment thus the activity in the tourist attraction providing real experience and role to the visitor or consumer with high expectations. This research uses qualitative methods where the informant is MSMEs authorities that operate in the sector of tourism village destination management which obtains challenges related how to promote and develop the destination branding through digital channels which currently, there is significant potential in terms of attracting customers. Based on the interview result, it is concluded that using sensory marketing potential to enhance consumer trust toward brands, particularly in the digital landscape aligned with market segment which is targeted, is evidenced by data indicating the increase of visiting before using sensory marketing strategy after applying sensory marketing strategy. Essentially sensory marketing activities that are capable of attracting interest are those that can be visualized on digital channels which can provide an incentive for further knowledge and trying to visit tourist destinations that are offered. Therefore, digital branding activities must collaborate with several activities that provide unforgettable memories through sensory marketing.